A inexistência de sucessão trabalhista nos cartórios extrajudiciais: uma situação peculiar - Arruda, Ana Luísa de Oliveira Nazar de (2007)
In the study developed in the present work, the aim was the approach of the various juridical aspects related with the notary, concluding at last for the inexistence of the labor succession by the person approved in the public context witch is an original administrative act. The particularities of the system juridical in which these notaries are based, mix public and private law principles and are not compatible with the application of the articles 10 and 448 of Consolidation of Labor Law. Finally, it is important to say that the focus of this work is not the already well known labor succession, normally discussed in books or courses based on the same theme, but a new and singular approach for a new and singular juridical reality of the notaries